Portable air purifier based on negative ions - Cai, Yiyang; Lu, Yifeng; Ni, Cong; Gao, Min; Lu, Chenhui; Zhang, Chunyan (IJRDO - Journal of Mechanical And Civil Engineering, 2019)
In recent years, negative ion generators have been widely used to solve increasingly serious air pollution problems. In order to alleviate the harmful effects of smog, a portable negative ion purifier is proposed. It can keep about 3 cubic meters of fresh air around the human body while helping children, women and the elderly, who are most vulnerable to respiratory diseases, avoid inhaling second-hand smoke. The purifier can make people breathe healthily and relieve fatigue. It can also greatly improve the quality of life and maintain the health of its users. This paper mainly describes the theoretical and practical research of this negative ion air purifier. Theoretical research includes the basic principles of negative ions and the rationality of design. Practical research includes a functional introduction of the various parts of the air purifier.